Hamstring injury occurrence in elite soccer players after preseason strength training with eccentric overload - Askling, C.; Karlsson, J.; Thorstensson, A. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The primary purpose of this study was to evaluate whether a preseason strength training programme for the hamstring muscle group - emphasising eccentric overloading - could affect the occurrence and severity of hamstring injuries during the subsequent competition season in elite male soccer players. Thirty players from two of the best premier-league division teams in Sweden were divided into two groups; one group received additional specific hamstring training, whereas the other did not. The extra training was performed 1-2 times a week for 10 weeks by using a special device aiming at specific eccentric overloading of the hamstrings. Isokinetic hamstring strength and maximal running speed were measured in both groups before and after the training period and all hamstring injuries were registered during the total observational period of 10 months. The results showed that the occurrence of hamstring strain injuries was clearly lower in the training group (3/15) than in the control group (10/15). In addition, there were significant increases in strength and speed in the training group. However, there were no obvious coupling between performance parameters and injury occurrence. These results indicate that addition of specific preseason strength training for the hamstrings - including eccentric overloading - would be beneficial for elite soccer players, both from an injury prevention and from performance enhancement point of view.